A critical evaluation of heteronuclear TOCSY (HEHAHA) experiments for 1H, 6Li spin pairs1. (28th August 2014) - Bergander, Klaus; Hüls, Dietmar; Glaser, Steffen J.; Günther, Harald; Luy, Burkhard
<x xml:space="preserve">Abstract</x> Heteronuclear TOCSY (HEHAHA) experiments for 1H, 6Li spin pairs in organolithium compounds with adjacent strongly coupled 1H, 1H spin systems showed unexpected cross peak behaviour: for n‐butyllithium 1H, 6Li cross peaks were completely missing, whereas for the dimer of (Z)‐2‐lithio‐1‐(o‐lithiophenyl)ethane, a cross peak for remote protons was observed even at very short mixing times. It was assumed that strong magnetization transfer within the proton spin systems was responsible for these results, which prevented unambiguous chemical shift assignments. Selective experiments with the 6Li, 1H‐HET‐PLUSH‐TACSY sequence then showed the expected 6Li, 1H cross peaks for the transfer via the directly coupled 1H and 6Li nuclei. For n‐butyllithium transfer to H(Cα) via an unresolved heteronuclear coupling constant below 0.1 Hz is unambiguously observed. Cross peaks in the 2D 6Li, 1H‐HET‐PLUSH‐TACSY spectra for the dimer of (Z)‐2‐lithio‐1‐(o‐lithiophenyl)ethane are readily explained by the measured coupling network and the corresponding active mixing conditions. Copyright © 2014 John Wiley & Sons, Ltd.